Interfacial Exchange Phenomena Driven by Ferromagnetic Domains (Adv. Mater. Interfaces 21/2022). Issue 21 (22nd July 2022) - Díez, José Manuel; Cuñado, José Luis F.; Lapa, Pavel; Solís, Raúl; Arnay, Icíar; Pedraz, Patricia; Perna, Paolo; Bollero, Alberto; Miranda, Rodolfo; Schuller, Ivan K.; Camarero, Julio
Abstract : Interfacial Exchange Phenomena Driven by Ferromagnetic Domains In article number 2200331, José Manuel Díez, José Luis F. Cuñado, Julio Camarero, and co‐workers demonstrate a new general mechanism controlling the exchange bias phenomena in antiferromagnetic/ferromagnetic (AFM/FM) heterostructures: the magnetic texture of the FM layer during reversal determines and controls the exchange bias, its temperature dependence, and other related phenomena. It allows to enhance the existing devices relying on exchange bias or to design innovative ones that were not possible before.